THE IDEOLOGY HIDDEN BEHIND THE FEMALE SONG LYRICS IS BEHIND THE VEIL OF KEKASIH GELAPKU SONG LYRICS - Ajid Mustopa; Suparna Suparna; Dede Abdurrohman (JLER (Journal of Language Education Research), 2020)
This research shows about the ideology hidden behind the song lyrics. The research method used is critical discourse analysis with analytical techniques using a substantive theoretical framework, namely hegemony, ideology, and feminism as well as the theory of study analysis from Michael Foucault. The results showed that the song was a study to marginalize one woman, but strengthen other women. The ability to reflect the listener's ideology towards patriarchal ideology, and use it as a force of encouragement that being the second is not bad.